Endotracheal tube intubation with the aid of a laryngeal mask airway, a fiberoptic bronchoscope, and a tube exchanger in a difficult airway patient: a case report - Sung, Joon Kyung (The Korean Society of Anesthesiologists, 2014)
A 28-year-old male patient with occipito-atlanto-axial instability underwent a cervical fusion with posterior technique. Post-operatively, the endotracheal tube (ETT) was removed, and the patient was transferred to the intensive care unit. After transfer, an upper airway obstruction developed and reintubations with a laryngoscope were attempted but failed. We inserted a #4 proseal laryngeal mask airway (LMA) and passed a 5.0 mm ETT through the LMA with the aid of a fiberoptic bronchoscope. We passed a tube exchanger through the 5.0 mm ETT and exchanged it with a 7.5 mm ETT. This method may be a useful alternative for difficult tracheal intubations.